Combinations of instruments to achieve low-carbon vehicle-miles - Don Fullerton; Daniel H. Karney (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2010)
Policymakers and economists have considered a number of different policies to reduce carbon emissions, including a carbon tax, a cap-and-trade permit system, a subsidy for the purchase or use of low-carbon vehicle technology, a renewable fuel standard, and mandates on manufacturers to increase the average fuel efficiency of the cars they sell. In this paper, we address issues in the use of these instruments separately or together. We consider the conditions under which policy makers should consider each such policy, and we show how the stringency of one such policy must depend upon the extent to which other such policies are already employed.
Keywords: 330